2005
DOI: 10.1063/1.2039085
|View full text |Cite
|
Sign up to set email alerts
|

The vibration-rotation emission spectrum of hot BeF2

Abstract: The high-resolution infrared emission spectrum of BeF2 vapor at 1000 degrees C was rotationally analyzed with the assistance of large-scale ab initio calculations using the coupled-cluster method including single and double excitations and perturbative inclusion of triple excitations, in conjunction with correlation-consistent basis sets up to quintuple-zeta quality. The nu3 fundamental band, the nu1+nu2, nu1+nu3, and 2nu2+nu3 combination bands, and 18 hot bands were assigned. The symmetric stretching (nu1), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…CO 2 , CS 2 , and BeF 2 are good examples of symmetric linear triatomic molecules for which experimental data are available for the 02 2 0͑⌬ g ͒ and 02 0 0͑⌺ g + ͒ states. [6][7][8] There is no ambiguity in the assignments for these molecules because to 152.3.102.242. Redistribution subject to AIP license or copyright; see http://jcp.aip.org/about/rights_and_permissions their 02 0 0͑⌺ g + ͒ states are in strong Fermi resonance with the nearby 10 0 0͑⌺ g + ͒ states, and thus lie much lower in energy compared with the 02 2 0͑⌬ g ͒ states.…”
mentioning
confidence: 96%
“…CO 2 , CS 2 , and BeF 2 are good examples of symmetric linear triatomic molecules for which experimental data are available for the 02 2 0͑⌬ g ͒ and 02 0 0͑⌺ g + ͒ states. [6][7][8] There is no ambiguity in the assignments for these molecules because to 152.3.102.242. Redistribution subject to AIP license or copyright; see http://jcp.aip.org/about/rights_and_permissions their 02 0 0͑⌺ g + ͒ states are in strong Fermi resonance with the nearby 10 0 0͑⌺ g + ͒ states, and thus lie much lower in energy compared with the 02 2 0͑⌬ g ͒ states.…”
mentioning
confidence: 96%
“…Comparison of the most precise to date experimental value of equilibrium r e (Be-F) = 1.3729710(95) Ǻ distance [24,25] with predictions of high-level QC calculation demonstrates slightly (within 0.01 Ǻ ) overestimated theoretical results. In the more recent FT IR study of BeF 2 , Yu et al [25] found the equilibrium distance 1.3730(1) Ǻ with one order larger error limit stated as that in earlier work [24,25]. In the early GED study of Akishin et al [4] published in 1958, though within large uncertainties of GED result typical for those days, the results are acceptably comparable with the contemporary GED data, except the case of BeI 2 .…”
Section: Beryllium Dihalidesmentioning
confidence: 83%
“…The MP2 method systematically underestimates this frequency. From the high-resolution infrared emission spectrum of hot, 1273 K, BeF 2 , Yu et al [25] determined the vibration frequencies for BeF 2 , m 1 = 769.0943(2), m 2 = 342.6145(3) and m 3 = 1555.0480(1) cm -1 , with unexpectedly low error limit declared. This work provides the first experimentally determined value of m 1 , and it is noticeably the larger ''harmonic'' theoretical values (Table 4).…”
Section: Beryllium Dihalidesmentioning
confidence: 98%
See 2 more Smart Citations